(untitled) (Architecture Image Studies, 2026)
This study aims to explore teachers’ perceptions regarding the integration of vocational orientation (VO) approaches and ICT in English language learning within vocational schools, with a particular focus on the collaboration between English teachers and vocational teachers. It uses a qualitative approach with a multi-case design in 7 vocational high schools in Kendari City, Indonesia. The data collection combines interviews from 28 informants, consisting of 7 English teachers, 7 vocational teachers, and 14 students. Besides that, classroom observation and document analysis were also conducted. The results of the study show that three themes emerge, namely: (1) the potential and benefits of integration; (2) student achievement; and (3) interdisciplinary collaboration. The informants have positive but realistic views. This perception is multi-layered. They consider that integrating English assignments with the place of work can be beneficial, especially when supported by ICT tools and teachers’ collaboration. There are common constraints such as time, internet access, and unclear roles in collaboration. Successful integration requires three essential elements, namely adequate access to ICT, collaborative structures through regular joint planning, and cross-disciplinary joint artifacts. If these three elements are met, the informant’s perception will merge and produce ESP learning that is authentic and relevant to the world of work.